2021
DOI: 10.1111/cns.13701
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a nomogram with EMP3 for predicting clinical outcomes in patients with glioma: A bi‐center study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
2
1
0
Order By: Relevance
“…Functional experiments showed that the knockdown of EMP3 significantly suppressed the malignant phenotype of tumor cells in terms of proliferation and migration. Consistent with other literature reports, Anke Zhang et al [ 32 ] demonstrated EMP3 as a novel predictor for clinical progression and clinical outcomes in glioma. However, what are the mechanisms and reasons behind it?…”
Section: Discussionsupporting
confidence: 89%
“…Functional experiments showed that the knockdown of EMP3 significantly suppressed the malignant phenotype of tumor cells in terms of proliferation and migration. Consistent with other literature reports, Anke Zhang et al [ 32 ] demonstrated EMP3 as a novel predictor for clinical progression and clinical outcomes in glioma. However, what are the mechanisms and reasons behind it?…”
Section: Discussionsupporting
confidence: 89%
“…[ 17 ] However, EMP3 is a tumor-suppressor gene of low-grade glioma (LGG). [ 18 ] In our present study, a high EMP3 expression was associated with poor survival, confirming that EMP3 is an oncogene. Studies have shown that the APOBEC3C expression positively affects the invasiveness and prognosis of breast cancer, glioma, hepatocellular carcinoma, and prostate cancer.…”
Section: Discussionsupporting
confidence: 84%
“…In previous studies, EMP3 [8] and CHI3L1 [24] were identified as novel independent predictors of clinical diagnosis, prognosis, and immune infiltration in glioma patients, respectively. In our study, we combined EMP3 and CHI3L1, which are correlated in glioma cells and can be combined as prognostic factors for patients with low-grade glioma.…”
Section: Discussionmentioning
confidence: 97%
“…Anke Zhang et al argued that aggressive treatment can impair a patient's quality of life and produce harmful adverse effects. Therefore, understanding the mechanisms underlying tumor progression is essential for disease management and prognosis prediction [8]. Gerber et al found that reduced mRNA expression levels of CHI3L1, EMP3, and other genes are associated with prolonged survival in glioma patients [9].…”
Section: Introductionmentioning
confidence: 99%